KONSEP RIBA DALAM ALQURAN DAN LITERATUR FIKIH - Mujar Ibnu Syarif (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2011)
The majority of commentators (jumhûr al-mufassirîn) argued that the reference of riba is a gift (al-‘athiyyah) of one person to another, not with the aim of reaching Allah's pleasure. However, riba was just to get a mere worldly rewards. The Qur'an did not explicitly mention the prohibition of riba. Therefore, the scholars differ on what is really meant by riba in Qur'an verses. Some scholars say the meaning of riba in the Quran is forbidden riba or riba nasî'ah. In this article, the concept of riba is studied based onthe Jurisprudence literatureDOI: